Public-private mix in health systems and repercussions for health inequalities in Latin American countries: A scoping review protocol - Eduarda Ferreira dos Anjos; Suelen Carlos de Oliveira; Adriana Mendoza-Ruiz; Maria del Pilar Flores-Quispe; Adelyne Maria Mendes Pereira; Carl Kendall; Ligia Regina Franco Sansigolo Kerr; Naiá Ortelan; Elzo Pereira Pinto Junior; Natalia Romero; Alastair Leyland; Maurício Lima Barreto; et al. (PLoS ONE, 2026)
Introduction Health system models in Latin American countries express differences in the state’s role in regulating, financing and providing health services, as well as in the coexistence of different care arrangements involving public and private entities. This scoping review will seek to identify evidence on how the different public-private configurations of health systems influence health inequalities in Latin America. Methods and analysis This protocol will be guided by the scoping review methodology developed by the Joanna Briggs Institute. The results will be presented according to the PRISMA-ScR protocol. Searches will be carried out on the Scielo, Lilacs, Embase, Pubmed, Web of Science and Scopus databases. The inclusion criteria will be publications whose central theme is the public-private mix of health systems in Latin America between January 2000 and March 2024. Exclusion criteria will be clinical trials, incomplete studies or in the design phase, duplicate publications, pre-print studies and gray literature (interim reports, unpublished texts, dissertations, and theses. The steps for carrying out the scope review will: (1) identifying the research question; (2) identifying relevant studies; (3) study selection; (4) charting the data; and (5) collating, summarizing, and reporting the results. Two independent reviewers will select the articles. The results will be described, analyzed, and categorized through narrative synthesis, correlating with the research objectives and questions. Expected results It is hoped that this scoping protocol will provide a comprehensive framework for investigating the gaps in the current literature on the public-private mix in Latin America and the effects on health inequalities. Link to the protocol record in the Open Science Framework (OSF): https://osf.io/rkzx3/?view_only=4594a2c52f2d47128d805fdd9dd1359b .